Monthly Active User Improvement in Social Media Mobile Phone Application: The Six Sigma Approach - Sulistia Fitriaty (Universitas Sebelas Maret, 2019)
This research study is focused on one social media that starts as an instant messaging app called ABC. ABC is an app originally from Southeast Asia that started to enter the Indonesian market in 2013. It has been struggling to maintain its monthly active user (MAU) during the past few months and wishes to get back on its feet as soon as possible. The problem occurred when it was unable to reach its MAU target which is 92 million in 2017. According to the control chart, it hasn’t quite made a significant improvement since the beginning of 2017. It is also incapable to meet the target. Several projects have been done just as usual to increase the number of MAU, but nothing happens. The number of MAU is going up and down without ever reaching the target. Based on 5 Whys Analysis, the root cause of the problem lies in two factors, the projects are held too often, and the company cannot specialize in each project based on specific target market criteria. The possible solution to implement is that the company should appoint someone to be the project planning coordinator. He or she will manage all executed projects so that they will align together to support company’s mission. Hence, increase the number of MAU as well. In conclusion, this study is aimed to improve the number of Monthly Active Users. This study will use Six Sigma approach to analyze deeply the problem being faced and come up with proposal solution for ABC App to implement in order to increase MAU. This study uses DMAIC method because the method is suitable to improve existing processes. The control phase will also be implemented by using FMEA Table. FMEA Table helps project planning coordinator to control each project so that further risks can be prevented in the beginning.